Multicultural Education: An Effort To Prevent Religious Radicalism In Indonesia - Anis Tanwir Hadi; Waston (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper was written due to the diversity among Indonesian people, whether diversity in religious, ethnic, racial, and cultural. Those diversities often have the potential to create various conflicts, along with the dynamics of the development of society that groups themselves in various socio-religious organizations and the initiates various religious thought streams. The purpose of writing this article was that through multicultural education, this paper was expected to provide alternative discourse solutions to prevent religious radicalism in Indonesia based on the values contained in Islamic teachings. This type of research could be classified as field research, which was considered as a broad approach in qualitative research or as a method for collecting qualitative data. Research approach or methodology of this study used a library approach. Data collection instruments were taken from readings related to the theme. In this case, multicultural Islamic education provided a spirit of enlightenment of religious life which was based on the values of unity, harmony, peace, tolerance, respect, and appreciation for differences and other attitudes that upheld the values of humanity and the spirit of the unity of the Indonesian people. The benefit of this paper was that multicultural Islamic education could be used as an approach or a new perspective as an alternative solution to change the way of thinking and the perspective of society as well as behavior in a plural society.